Circularly polarized slotted-ground microstrip antennas for radiofrequency identification readers - Nasimuddin. (2013)
The single-feed, circularly polarized microstrip antennas (CPMAs) based on the slotted-ground plane are investigated for radiofrequency identification readers.The conventional CPMA with truncated corners is also studied to compare with the proposed CPMA's performances. In the proposed designs, four square slots with asymmetrical configuration are etched in the diagonal directions on the ground plane of the antenna to achieve circularly polarized radiation. The proposed CPMAs are designed with low-cost FR4 substrate and RO4003C substrate and their performances are compared. The antenna bandwidth is also studied on thin and thick dielectric substrates.